Culture and Identity 2018
DOI: 10.5772/intechopen.74411
|View full text |Cite
|
Sign up to set email alerts
|

Popular Religions and Multiple Modernities: A Non-Western Perspective

Abstract: Religious diversity and pluralism is increasing all over the world, and globalization is creating a widespread awareness of that. The growing influence of religions in public politics and culture around the world is contradicting conventional narratives of secularization. Indeed, the resurgence of religions in all the continents is tangled in different ways to modernization processes. The main argument of this chapter is that this religious change toward pluralism can be fully understood in the context of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Previous studies have shown that religion is positively related to happiness and reduced stress [16,17]. This is more evident in non-western countries as religion can play a more significant role in the cultural and social aspects of life for people living in those countries [18]. In the case of Iranian elders, studies have determined that religious beliefs can reduce death anxiety [19] and can be an essential aspect of an older adult's sense of power [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that religion is positively related to happiness and reduced stress [16,17]. This is more evident in non-western countries as religion can play a more significant role in the cultural and social aspects of life for people living in those countries [18]. In the case of Iranian elders, studies have determined that religious beliefs can reduce death anxiety [19] and can be an essential aspect of an older adult's sense of power [20].…”
Section: Introductionmentioning
confidence: 99%
“…22-25). Mainstream theory has not significantly departed from the old pattern (Bender et al 2013), though it is being chewed around the edges by feminists (Neitz 2000; Goldman 2012), scholars of "lived religion" (Hall 1997;Ammerman 2007;, those investigating religion in 'non-religious' places (Bender 2003;Cadge 2013;Gauthier 2013), and Latin American advocates of "popular religion" as the road to understanding religion's future (Parker 1996(Parker , 2018de la Torre and Martín 2016).…”
Section: Religion and Sociology's Originsmentioning
confidence: 99%
“…Though religious statistics emphasize the relative non-religiousness of that region (Pew Research Center 2015b), this view reflects the lack of official religious membership (Hackett et al 2015). In addition, there are many traditional East Asian practices that present themselves as philosophies and not religions in the Western sense (Ma and Meng 2011;Yeung 2003;Parker 2018). Indeed, popular religion in China has often been studied under a Western-oriented optic, with magic having a predominant role (Weber 1951).…”
Section: Popular Religions Within Multiple Modernitiesmentioning
confidence: 99%
“…In Latin America, the classical folk religion (traditional, peasant, rural, illiterate, and pre-modern) is no longer predominant, although it can be found in many African and Asian countries. Yet it is indisputable that there are many vital popular religions in the heart of the megacity, in the urban core of multiple modernities (Parker 2018).…”
Section: Popular Religions Within Multiple Modernitiesmentioning
confidence: 99%